Proceedings of the 12th ACM/IEEE International Symposium on Empirical Software Engineering and Measurement 2018
DOI: 10.1145/3239235.3240501
|View full text |Cite
|
Sign up to set email alerts
|

Identifying unmaintained projects in github

Abstract: Background: Open source software has an increasing importance in modern software development. However, there is also a growing concern on the sustainability of such projects, which are usually managed by a small number of developers, frequently working as volunteers. Aims: In this paper, we propose an approach to identify GitHub projects that are not actively maintained. Our goal is to alert users about the risks of using these projects and possibly motivate other developers to assume the maintenance of the pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…The recent work by Coelho et al [23] presented a machine learning based approach that uses standard metrics (number of commits, pull requests, contributors, etc.) extracted from Github to classify, whether maintenance of a particular project becomes dead.…”
Section: Maintenance Of Software Librariesmentioning
confidence: 99%
“…The recent work by Coelho et al [23] presented a machine learning based approach that uses standard metrics (number of commits, pull requests, contributors, etc.) extracted from Github to classify, whether maintenance of a particular project becomes dead.…”
Section: Maintenance Of Software Librariesmentioning
confidence: 99%
“…Another problem being solved by this researcher was identifying which of the seemingly abandoned projects may be "feature complete," i.e. already have the intended scope and do not require further maintenance [13]. Feature complete projects should be widely used in contrast to abandoned projects.…”
Section: Python Ecosystem Analysismentioning
confidence: 99%
“…Feature complete projects should be widely used in contrast to abandoned projects. Proxies of project usage, e.g., GitHub stars or forks can be used to identify such projects [13]. WoC, however, lets us measure the extent of use directly.…”
Section: Python Ecosystem Analysismentioning
confidence: 99%
“…The reasons for the high acceptance of this issue includes a complete rework of the framework's API and the addition of long-standing feature requests. By contrast, the issue "Changing Redis master-slave replication terms with something else", 6 which was created by the repository owner, received the highest number of Thumbs down and Confused reactions. According to the comments in this issue, the proposal does not add value to the project and causes compatibility issues with previous versions.…”
Section: Rq #2: What Are the Most Common Reactions?mentioning
confidence: 99%
“…Borges et al [3] investigated the characteristics of popular GitHub repositories and found four major popularity growth patterns. Recently, Coelho et al [6] proposed an approach to identify unmaintained projects in GitHub. Their approach apply machine learning techniques and rely on metrics that measure the maintained level to identify and alert users.…”
Section: Related Workmentioning
confidence: 99%